Educational Policy Analysis: Examining Pesantren Policies and Their Implications on the Independence of Kyai and Pesantren in the Contemporary Era - Nadhif Muhammad Mumtaz; Evi Muafiah; Doli Witro (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This study aims to investigate the autonomy of “Kyai” (religious teachers) within Pesantren in making education policy. In examining these policies, it focuses on the evolution of teaching and the implementation of the “Asas Tunggal Pancasila” in Indonesian educational institutions, the struggles of Pesantren policies that led to the birth of Law No. 18 of 2019, and the dark side of the politicization of religion that has implications for educational policies. Design/methods/approach – This type of research uses qualitative research with a case study of two Islamic boarding schools in East Java (research objects). Primary data sources come from observation and interview results. Secondary data sources come from library sources such as laws, scientific articles (journals), books, etc. Data collection used observation techniques, semi-structured in-depth interviews, and documentation (document analysis). Data analysis techniques used qualitative data analysis techniques, namely data condensation, data presentation, and conclusion drawing. Findings – The research reveals that the law empowers Pesantren and Kyai to shape their institutions in alignment with societal demands, traditions, and evolving times. Though the Kyai’s independence significantly affects the Pesantren’s trajectory, it does not singularly define its identity. The law underscores the imperative for contemporary teaching methods, curriculum evolution, and infrastructure enhancement, urging Kyai to eschew rigid and authoritarian stances. Research implications/limitations – The research has theoretical implications that two contrasting views concerning Pesantren policies’ influence on Kyai’s independence vis-à-vis political elites. Proponents (“Yes”) highlight Alignment of Interest, Empowerment and Development, and Community Engagement. Opponents (“No”) cite the Preservation of Autonomy, the potential for manipulation, and an inherent distrust of political parties. Originality/value – The research provides direction for the complex interplay between religious education and the political domain in Indonesia.